2020
DOI: 10.31436/imjm.v17i2.271
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Salivary Flow Rate and pH in Patients with Recurrent Oral Ulcers

Abstract: Introductions: Recurrent oral ulcers primarily effect mucosal surfaces and are among the most common chronic inflammatory diseases. Numerous studies to find the aetiopathogenesis have been conducted however the cause still remains unclear. Saliva is of utmostimportance for oral health maintenance. In current study, saliva was used as a diagnostic tool for comparison of salivary flow rate and pH in patients suffering from recurrent oral ulcers and control group. Materials and Methods: Saliva samples taken from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Studies have shown that dog saliva is more alkaline than human saliva; therefore, it may have a higher buffering capacity for acids (Al‐Ahmad et al., 2018 ; Lavy et al., 2012 ). The lack of reports on significant enamel loss in dogs treated with clopidogrel is attributed to the buffering ability of saliva.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that dog saliva is more alkaline than human saliva; therefore, it may have a higher buffering capacity for acids (Al‐Ahmad et al., 2018 ; Lavy et al., 2012 ). The lack of reports on significant enamel loss in dogs treated with clopidogrel is attributed to the buffering ability of saliva.…”
Section: Discussionmentioning
confidence: 99%
“…Dental erosion refers to the loss of enamel due to acquired causes, and the most prominent etiological factor in humans is known to be low pH (Barbour et al., 2011 ). Dog saliva has a pH of 8.5, making it more alkaline and resulting in a higher buffering capacity compared to human saliva (pH 6.2–7.6) (Al‐ahmad et al., 2018 ; Lavy et al., 2012 ). This difference in saliva composition between humans and dogs is thought to be the reason why caries or erosion are less common in dogs (Pasha et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In healthy individuals, the pH of saliva varies between 6.20 and 7.60 (Al et al, 2018 ) and is maintained at a non‐harmful level to the oral cavity through three buffer systems (bicarbonate, phosphate, and protein) (Dawes et al, 2015 ), depending and being strongly associated with the salivary secretion flow (Aframian et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%